De novo, heterozygous, loss‐of‐function mutations in SYNGAP1 cause a syndromic form of intellectual disability. (15th June 2015) - Parker, Michael J.; Fryer, Alan E.; Shears, Deborah J.; Lachlan, Katherine L.; McKee, Shane A.; Magee, Alex C.; Mohammed, Shehla; Vasudevan, Pradeep C.; Park, Soo‐Mi; Benoit, Valérie; Lederer, Damien; Maystadt, Isabelle; et al.
Abstract : De novo mutations (DNM) in SYNGAP1, encoding Ras/Rap GTPase‐activating protein SynGAP, have been reported in individuals with nonsyndromic intellectual disability (ID). We identified 10 previously unreported individuals with SYNGAP1 DNM; seven via the Deciphering Developmental Disorders (DDD) Study, one through clinical analysis for copy number variation and the remaining two (monozygotic twins) via a research multi‐gene panel analysis. Seven of the nine heterozygous mutations are likely to result in loss‐of‐function (3 nonsense; 3 frameshift; 1 whole gene deletion). The remaining two mutations, one of which affected the monozygotic twins, were missense variants. Each individual carrying a DNM in SYNGAP1 had moderate‐to‐severe ID and 7/10 had epilepsy; typically myoclonic seizures, absences or drop attacks. 8/10 had hypotonia, 5/10 had significant constipation, 7/10 had wide‐based/unsteady gait, 3/10 had strabismus, and 2/10 had significant hip dysplasia. A proportion of the affected individuals had a similar, myopathic facial appearance, with broad nasal bridge, relatively long nose and full lower lip vermilion. A distinctive behavioral phenotype was also observed with aggressive/challenging behavior and significant sleep problems being common. 7/10 individuals had MR imaging of the brain each of which was reported as normal. The clinical features of the individuals reported here show significant overlap with those associated with 6p21.3 microdeletions, confirming that haploinsufficiency for SYNGAP1 is responsible for both disorders. © 2015 The Authors. American Journal of Medical Genetics Part A Published by Wiley Periodicals, Inc.